Progress in particular fields of fusion technology presented at the 29th IAEA Fusion Energy Conference 2023 - Klaus Hesch (Nuclear Fusion)
This paper provides an overview on the progress in fusion technologies presented during the 29th IAEA Fusion Energy Conference held in October 2023 at London, UK, with a focus on the topics ITER technology, heating and current drive technology as well as fusion nuclear technology, including fusion nuclear science as well as technology research devices. A complementary contribution, authored by Amanda Quadling, covers the topics materials development, in-vessel components, licensing & safety, socio-economics and environment, as well as next step machine designs.